2019
DOI: 10.1002/csr.1810
|View full text |Cite
|
Sign up to set email alerts
|

Nonfinancial risk disclosure: The “state of the art” of Italian companies

Abstract: This research represents a preliminary analysis of the nonfinancial risk disclosure and the first after the introduction of the European directive. Using a content analysis, the level of nonfinancial risk disclosure after the introduction of the Directive 2014/95/EU on nonfinancial information has been investigated. Moreover, in order to understand the effectiveness of nonfinancial risk management, the outlook orientation (past, present, and future) and the approach to risk (positive, negative, and neutral) ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
83
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 70 publications
(94 citation statements)
references
References 49 publications
10
83
1
Order By: Relevance
“…With reference to the topic of NFI, generally, extant literature does not find unanimous agreement on the potential benefits deriving from more or improved regulation [11,18,19]. In fact, some scholars call for further investigation of the effect of the disclosure of nonfinancial risks [4,20]. Moreover, in a context of mandated disclosure, Dobler [21] observed that companies tend to disclose mainly information on their financial risks.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…With reference to the topic of NFI, generally, extant literature does not find unanimous agreement on the potential benefits deriving from more or improved regulation [11,18,19]. In fact, some scholars call for further investigation of the effect of the disclosure of nonfinancial risks [4,20]. Moreover, in a context of mandated disclosure, Dobler [21] observed that companies tend to disclose mainly information on their financial risks.…”
Section: Introductionmentioning
confidence: 99%
“…In the literature, we can observe a further gap concerning the scarcity of empirical evidence about the potential benefits of the disclosure of NFI in the stakeholder perspective. In particular, the relationship between risk disclosures and firm value is underresearched, as the NFI literature mainly focuses on the motivations supporting the companies' decision to disclose [4,20,22].…”
Section: Introductionmentioning
confidence: 99%
“…Among studies focused on nonfinancial risks disclosure in general terms, Dumay and Hossain [33] investigated the sustainability risk mandatory disclosure practices of listed companies in Australia and two studies based on the Italian context, one before the EU transposition introduced Decree No. 254/2016 [5] and one after this decree [43].…”
Section: Prior Literature On the Determinants Of Risk-related Disclosmentioning
confidence: 99%
“…However, past research mainly focused on the disclosure of financial risk in countries where the disclosure was mandatory [43], and the usefulness of risk disclosure for stakeholders, as well as the extent of risk disclosure, have been investigated mainly with reference to financial risks [36,44,45] and its usefulness for investors [35,46]. On the contrary, the disclosure of nonfinancial risks has been scarcely investigated [45], and only recently, theoretical and empirical studies have started to investigate sustainability risk disclosure [47].…”
Section: Prior Literature On the Determinants Of Risk-related Disclosmentioning
confidence: 99%
“…Also, very few studies examining the effects of social, environmental, and sustainable disclosure in the EU banking sector have so far been published (Avrampou, Skouloudis, Iliopoulos, & Khan, ; Fijałkowska et al, 2017; Forcadell & Aracil, ; Rogošić, ; Carnevale, Mazzuca, & Venturini, ; Branco & Rodrigues, ). This paper can therefore be of use to regulatory bodies (Cormier, Ledoux, & Magnan, ; Deegan, ; Freedman & Jaggi, ), organizations (Coupland, ; Gray, Kouhy, & Lavers, ; Gray, Javad, Power, & Sinclair, ; Halme & Huse, 1997; Hackston & Milne, 1996; Lindblom, ;), the banking sector, and the stakeholders involved (Kudratova, Huang, Kudratov, & Qudratov, ; Alniacik, Alniacik, & Genc, ; Campra and Esposito, 2018; Venturelli, Cosma, & Leopizzi, ; Leopizzi, Iazzi, Venturelli, & Principale, ; Clarkson, ).…”
Section: Introductionmentioning
confidence: 99%